Corporate Social Responsibility Practices in India: A Study of Few Companies: Analyzing Corporate Social Responsibility Practices in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper seeks to identify the Corporate Social Responsibility practices followed by companies operating in India. This paper will help the researchers and scholars in identifying the best CSR practices and to do further studies on what is best for India and what India really needs as CSR from the corporate. Indian Government has made CSR mandatory for the companies having turnover or benefits beyond a farthest point. Companies Act 2013 includes the arrangements related to CSR for the companies. Corporate Social Responsibility (CSR) isn't just a legal arrangement, however it is a commitment also with respect to an organization. As the companies begin their operations in the society, for the society and from different resources provided by the society, it becomes critical for them to give something in return to the society. This paper further seeks to identify the failures of companies in meeting the expectations of the society and helps to provide some suggestions to improve the CSR practices to better serve the society and the country on the loose.